Effect of General Anesthesia on Levels of Blood Sugar Values in Different Times of Operation (Medico Legal Update, 2021)
The present study was carried out on a period between December 2019 to February 2020 on 50 healthypatients, their ages ranged from eighteen to fifty years. They were 26 males and 24 females. These healthypatients were attending Baghdad Educational Hospital, Al-Harriri Hospital, and Al-Diwaniyah GeneralHospital in order to perform various surgeries. And after all tests are done. Then they were admitted to theoperating theater. In this study used the general anesthesia method. And they were given drugs of anesthesia,during each step; the values of blood sugar levels (Mg\dl) were measured. Such as pre induction, postinduction, after incision, after fluid, and recovery. To know the effect of general anesthesia method on bloodsugar levels in different times of operation on gender and age groups.This study showed that total numbers of patients were 50 including males about 26 (52.0%) and femalesabout 24(48.0%), their age of all individuals ranged from less than 20 years old (